2022
DOI: 10.1111/jcmm.17595
|View full text |Cite
|
Sign up to set email alerts
|

The effects of FTO gene rs9939609 polymorphism on the association between breast cancer and dietary intake

Abstract: Breast cancer (BC) is the leading cause of cancer‐related deaths in females worldwide and is related to genetic and environmental factors. Dietary components may strongly influence the risk of BC. A possible association was also reported between the fat mass and obesity‐associated (FTO) single‐nucleotide polymorphisms (SNPs) and BC. This study aimed to investigate the impact of FTO rs9939609 polymorphism on the association between BC and dietary intake. This study was conducted on 180 women with BC as the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Recent genome-wide association studies have identified several SNPs associated with high BMI and BC ( Table 3 ). The FTO alpha-ketoglutarate-dependent dioxygenase ( FTO ) gene was reported to be associated with obesity [ 177 ]. FTO was found to be involved in appetite and food intake [ 178 , 179 ].…”
Section: The Genetic Interactions Of Obesity With Bc Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genome-wide association studies have identified several SNPs associated with high BMI and BC ( Table 3 ). The FTO alpha-ketoglutarate-dependent dioxygenase ( FTO ) gene was reported to be associated with obesity [ 177 ]. FTO was found to be involved in appetite and food intake [ 178 , 179 ].…”
Section: The Genetic Interactions Of Obesity With Bc Riskmentioning
confidence: 99%
“…The FTO SNP rs9939609 was correlated with BC and the effect status of ERs and the PI3K/Akt signaling pathway [ 31 ]. A case-control study by Doaei et al found a significant positive association between BC and dietary fat intake in women with the risk allele of FTO SNP rs9939609 [ 177 ].…”
Section: The Genetic Interactions Of Obesity With Bc Riskmentioning
confidence: 99%